Završnik, A. and Simončič, K. (Εds.) (2023). Artificial Intelligence, social harms and human rights. Palgrave Macmillan (XIV+276 pages). ISBN: 978-3-031-19148-0. https://doi.org/10.1007/978-3-031-19149-7. - Gotsis, George (The Greek Review of Social Research, 2024)
Ν/Α